The effect of simulated natural environments in virtual reality and 2D video to reduce stress - Suseno, Bayu; Hastjarjo, Thomas Dicky (Frontiers in Psychology, 2023)
Stress is a common problem associated with poor physical and psychological health. Exposure to the natural environment is one method for reducing stress. The real and simulated natural environments have a restorative effect on stress reduction. In contrast to the real environment, simulated natural environments, such as virtual reality and 2D video, provide safer and more controllable exposure. Several studies on the restorative effects of the natural environment in virtual reality and 2D video have been conducted. However, the difference between the two in reducing stress must be clarified. This study was conducted to determine the effect of the simulated natural environments in virtual reality and 2D video and their differences in reducing stress. This study hypothesizes that both simulated natural environments in virtual reality and 2D video can reduce stress, but there is a difference between them in reducing stress. Fifty-three subjects were divided into two experimental groups: 2D video (n = 28) and virtual reality (n = 25). The results indicated that simulated natural environments in virtual reality and 2D video reduced stress. However, there was no difference between the two groups regarding stress reduction.